Paeonol Protects Against Methotrexate-Induced Nephrotoxicity via Upregulation of P-gp Expression and Inhibition of TLR4/NF-κB Pathway - Mohamed A. Morsy; Mohamed A. Morsy; Azza A. K. El-Sheikh; Azza A. K. El-Sheikh; Sara Mohamed Naguib Abdel-Hafez; Mahmoud Kandeel; Mahmoud Kandeel; Seham A. Abdel-Gaber (Frontiers Media S.A., 2022)
Methotrexate (MTX) is a well-known anticancer drug that causes nephrotoxicity as a side effect. To investigate the mechanisms by which paeonol, a natural phenolic compound, can protect against MTX-induced nephrotoxicity, paeonol (100 mg/kg/day orally) was given to rats for 10 days, with or without MTX (20 mg/kg once i.p. at day 5). Compared to control, MTX caused nephrotoxic effects manifested by increased serum urea and creatinine and distortion in renal histological architecture, with a significant increase in the mean glomerular diameter and upregulation of kidney injury molecule-1. MTX caused oxidative stress manifested by decreasing reduced glutathione and superoxide dismutase while increasing malondialdehyde and nitric oxide. MTX also induced renal inflammation by upregulating TLR4, NF-κB, and IL-1β and caused apoptosis by induction of caspase 3. Administering paeonol with MTX improved kidney functional and structural parameters, as well as all oxidative, inflammatory, and apoptotic markers tested. Interestingly, both MTX and paeonol increased the expression of the renal efflux transporter P-glycoprotein (P-gp) that helps in MTX elimination, and their drug combination further upregulated renal P-gp. In silico, paeonol was neither a substrate nor an inhibitor of P-gp, suggesting that its effect on P-gp is not on functional but on the expression level. In vitro, paeonol and MTX were administered to colon cancer cells and their combination caused a progressive cellular cytotoxic effect, which was dose-dependent with the increase of paeonol concentration. In conclusion, paeonol protects against MTX-induced nephrotoxicity through antioxidant, anti-inflammatory, and antiapoptotic mechanisms and might potentiate MTX chemotherapeutic efficacy.